Gender identity X “gender ideology”: a historical analysis of post-1988 education legal documents (Olhar de Professor, 2023)
This article deals with the mistaken use of the concept “Gender ideology” and its consequences in education. The term, which gained strength in Brazil with the emergence of the “Escola Sem Partido” in 2004, which advocates a traditional, heteronormative and patriarchal family, has been used by conservative groups to criticize the teaching of issues related to sexual and gender diversity in schools. schools. In addition, these groups see the discussion of sensitive issues as a threat to the traditional and conservative view. The article starts from a case study that took place in the city of Porto Alegre, Rio Grande do Sul, and seeks to demonstrate how the use of this concept can lead to serious consequences, such as the dismissal of a teacher. It also discusses how the conservative discourse has influenced educational legislation, leading to the omission of the words gender and gender identity in legal documents, analyzing from the 1988 Constitution to the BNCC (2017). Such research is of an analytical documental nature, and seeks to compare official sources with conservative discourses, which guided the removal of the concepts of gender identity and gender from the legal documents of education. This study shows the progress of the conservative current in educational guidelines, in such a way that it was possible to verify the suppression of the word gender and gender identity in legal documents, and defends the importance of an inclusive education that respects diversity, alerting to the dangers of using misconceptions to restrict debate and reflection on sensitive issues.
Keywords: Gender; Gender Identify; Gender Ideology; Education